2007
DOI: 10.1590/s0101-74382007000100007
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic control charts with two-stage sampling for monitoring bivariate processes

Abstract: In this article, we consider the synthetic control chart with two-stage sampling (SyTS chart) to control bivariate processes. During the first stage, one item of the sample is inspected and two correlated quality characteristics ( x; y ) are measured. If the Hotelling statistic 2 1 T for these individual observations of ( x; y ) is lower than a specified value 1 UCL the sampling is interrupted. Otherwise, the sampling goes on to the second stage, where the remaining items are inspected and the Hotelling statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Their numerical comparisons showed that the autocorrelation has a negative effect on the side‐sensitive schemes and they are inferior to the usual S1 T 2 chart, especially for variables with a high correlation coefficient. Costa and Machado considered a correlated bivariate process using a two‐stage sampling procedure with a S1 T 2 chart. More recently, Dargopatil and Ghute proposed a multivariate analogue of Hu and Sun using skipping and mixed sampling strategies to reduce the negative effect of autocorrelation.…”
Section: Multivariate Synthetic Chartsmentioning
confidence: 99%
“…Their numerical comparisons showed that the autocorrelation has a negative effect on the side‐sensitive schemes and they are inferior to the usual S1 T 2 chart, especially for variables with a high correlation coefficient. Costa and Machado considered a correlated bivariate process using a two‐stage sampling procedure with a S1 T 2 chart. More recently, Dargopatil and Ghute proposed a multivariate analogue of Hu and Sun using skipping and mixed sampling strategies to reduce the negative effect of autocorrelation.…”
Section: Multivariate Synthetic Chartsmentioning
confidence: 99%
“…Control charts are statistical procedures that have been generally utilized in checking item quality during the production process. More insights regarding the usual control chart can be found in Costa and Machado (2007) and Claro et al (2008). Schilling and Neubauer (2017) suggested that the reliability sampling plans are utilized to decide the adequacy of the item at some future point in its operational life.…”
Section: Introductionmentioning
confidence: 99%
“…Many innovations have been proposed to improve the performance of the T 2 charts. Costa and Machado (2007) studied the properties of the synthetic T 2 chart with two-stage sampling. Machado and Costa (2008b) considered the use of simultaneous X charts as an alternative to the use of the T 2 chart.…”
Section: Introductionmentioning
confidence: 99%